Answer:
![2.09\ \text{m/s}](https://tex.z-dn.net/?f=2.09%5C%20%5Ctext%7Bm%2Fs%7D)
![22298.4\ \text{J}](https://tex.z-dn.net/?f=22298.4%5C%20%5Ctext%7BJ%7D)
Explanation:
m = Mass of each the cars = ![1.6\times 10^4\ \text{kg}](https://tex.z-dn.net/?f=1.6%5Ctimes%2010%5E4%5C%20%5Ctext%7Bkg%7D)
= Initial velocity of first car = 3.46 m/s
= Initial velocity of the other two cars = 1.4 m/s
v = Velocity of combined mass
As the momentum is conserved in the system we have
![mu_1+2mu_2=3mv\\\Rightarrow v=\dfrac{u_1+2u_2}{3}\\\Rightarrow v=\dfrac{3.46+2\times 1.4}{3}\\\Rightarrow v=2.09\ \text{m/s}](https://tex.z-dn.net/?f=mu_1%2B2mu_2%3D3mv%5C%5C%5CRightarrow%20v%3D%5Cdfrac%7Bu_1%2B2u_2%7D%7B3%7D%5C%5C%5CRightarrow%20v%3D%5Cdfrac%7B3.46%2B2%5Ctimes%201.4%7D%7B3%7D%5C%5C%5CRightarrow%20v%3D2.09%5C%20%5Ctext%7Bm%2Fs%7D)
Speed of the three coupled cars after the collision is
.
As energy in the system is conserved we have
![K=\dfrac{1}{2}mu_1^2+\dfrac{1}{2}2mu_2^2-\dfrac{1}{2}3mv^2\\\Rightarrow K=\dfrac{1}{2}\times 1.6\times 10^4\times 3.46^2+\dfrac{1}{2}\times 2\times 1.6\times 10^4\times 1.4^2-\dfrac{1}{2}\times 3\times 1.6\times 10^4\times 2.09^2\\\Rightarrow K=22298.4\ \text{J}](https://tex.z-dn.net/?f=K%3D%5Cdfrac%7B1%7D%7B2%7Dmu_1%5E2%2B%5Cdfrac%7B1%7D%7B2%7D2mu_2%5E2-%5Cdfrac%7B1%7D%7B2%7D3mv%5E2%5C%5C%5CRightarrow%20K%3D%5Cdfrac%7B1%7D%7B2%7D%5Ctimes%201.6%5Ctimes%2010%5E4%5Ctimes%203.46%5E2%2B%5Cdfrac%7B1%7D%7B2%7D%5Ctimes%202%5Ctimes%201.6%5Ctimes%2010%5E4%5Ctimes%201.4%5E2-%5Cdfrac%7B1%7D%7B2%7D%5Ctimes%203%5Ctimes%201.6%5Ctimes%2010%5E4%5Ctimes%202.09%5E2%5C%5C%5CRightarrow%20K%3D22298.4%5C%20%5Ctext%7BJ%7D)
The kinetic energy lost during the collision is
.
False: because atoms are base on the elements on the periodic table.
Answer:
Yes, it's correct
Explanation:
Newton's second Law states that the acceleration of an object is proportional to the net force applied on it, according to the equation:
![F=ma](https://tex.z-dn.net/?f=F%3Dma)
where
F is the net force on the object
m is the mass of the object
a is the acceleration of the object
We can re-arrange the previous equation in order to solve explicitely for a, the acceleration, and we find:
![F=ma\\\frac{F}{m}=\frac{ma}{m}\\\frac{F}{m}=a\\a=\frac{F}{m}](https://tex.z-dn.net/?f=F%3Dma%5C%5C%5Cfrac%7BF%7D%7Bm%7D%3D%5Cfrac%7Bma%7D%7Bm%7D%5C%5C%5Cfrac%7BF%7D%7Bm%7D%3Da%5C%5Ca%3D%5Cfrac%7BF%7D%7Bm%7D)
So, we see that the acceleration is proportional to the net force and inversely proportional to the mass of the object.